Strategic communication across languages in business environments: A study of the language management strategies of small and medium-sized enterprises on the island of Ireland. Issue 1 (1st April 2022) - Bruen, Jennifer; Buckley, Finian
Abstract : There has been little research focusing on how small and medium-sized enterprises (SMEs), particularly those in anglophone contexts, approach language management with a resultant lack of understanding hindering language policymaking at national levels. Therefore, this study assesses the extent to which a sample of thirty-eight SMEs, fifteen in the Republic of Ireland (RoI) and twenty-three in Northern Ireland, have a language management strategy (LMS), that is, a plan of action enabling them to communicate across languages with suppliers and/or customers abroad. The survey also explored the attitudes of the SMEs toward adopting a strategic approach to language management focusing on four interrelated elements: first, whether the SMEs felt they needed an LMS; second, how effective they regarded their communication with speakers of languages other than English to be; third, their views on whether they had missed a business opportunity owing to a lack of language capacity; and fourth their perceptions regarding whether language was a factor in choosing export markets or suppliers. The results indicate that 16% of the SMEs report having an LMS, 33% of those in the RoI and 4% of those in Northern Ireland (NI). The analysis of the responses further revealed that 45% of all respondents engaged, in some form, with languages other than English, albeit often in an apparently ad hoc manner. The article discusses the findings and considers the supports and policy initiatives likely to assist SMEs in developing LMSs in these predominantly anglophone (European Union and non-European Union) contexts.